2017
DOI: 10.1248/bpb.b16-00989
|View full text |Cite
|
Sign up to set email alerts
|

The Safety Profile of Telaprevir-Based Triple Therapy in Clinical Practice: A Retrospective Cohort Study

Abstract: This study was designed to evaluate the safety profile of adding telaprevir to therapy using pegylated interferon-alfa-2b and ribavirin (PR) using real world patient data obtained from a nationwide Japanese interferon database. This retrospective cohort study compared telaprevir-based triple therapy (T/PR) with PR therapy. The study population comprised patients with genotype 1 chronic hepatitis C represented in the database between December 2009 and August 2015. The primary endpoint was dropout from treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Age, HCV viral load and platelet count were classified according to the guidelines of The Japan Society of Hepatology, 4) these factors having previously been identified as contributing to the differential rate of treatment discontinuation for T/PR versus PR. 14) We also considered treatment experience as a covariate based on previously published guidelines 10) that recommend physicians consider treatment experience when deciding which therapy to provide to a patient. Model performance was assessed using the C-index, with a C-index of '1′ indicative of a perfect discrimination between the T/PR and PR groups, with an index >0.8 recommended to calculate a PS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, HCV viral load and platelet count were classified according to the guidelines of The Japan Society of Hepatology, 4) these factors having previously been identified as contributing to the differential rate of treatment discontinuation for T/PR versus PR. 14) We also considered treatment experience as a covariate based on previously published guidelines 10) that recommend physicians consider treatment experience when deciding which therapy to provide to a patient. Model performance was assessed using the C-index, with a C-index of '1′ indicative of a perfect discrimination between the T/PR and PR groups, with an index >0.8 recommended to calculate a PS.…”
Section: Methodsmentioning
confidence: 99%
“…13) As an example, a real-world study reported a lower discontinuation rate for T/PR than for PR therapy. 14) Of clinical relevance is the evaluation of HCV therapy in elderly individuals in whom the risk for HCV is specifically higher than in younger adults 15) and yet, this segment of the population is generally excluded from clinical trials. This issue is of relevance in Japan, where the proportion of elderly in the general population is significantly higher than in Europe and the United States.…”
Section: )mentioning
confidence: 99%